Derivation of ecological criteria for copper in land-applied biosolids and biosolid-amended agricultural soils. (1st December 2016) - Lu, Tao; Li, Jumei; Wang, Xiaoqing; Ma, Yibing; Smolders, Erik; Zhu, Nanwen
Abstract: The difference in availability between soil metals added via biosolids and soluble salts was not taken into account in deriving the current land-applied biosolids standards. In the present study, a biosolids availability factor (BAF) approach was adopted to investigate the ecological thresholds for copper (Cu) in land-applied biosolids and biosolid-amended agricultural soils. First, the soil property-specific values of HC5add (the added hazardous concentration for 5% of species) for Cu 2+ salt amended were collected with due attention to data for organisms and soils relevant to China. Second, a BAF representing the difference in availability between soil Cu added via biosolids and soluble salts was estimated based on long-term biosolid-amended soils, including soils from China. Third, biosolids Cu HC5input values (the input hazardous concentration for 5% of species of Cu from biosolids to soil) as a function of soil properties were derived using the BAF approach. The average potential availability of Cu in agricultural soils amended with biosolids accounted for 53% of that for the same soils spiked with same amount of soluble Cu salts and with a similar aging time. The cation exchange capacity was the main factor affecting the biosolids Cu HC5input values, while soil pH and organic carbon only explained 24.2 and 1.5% of the variation, respectively. The biosolids Cu HC5input values can be accurately predicted by regression models developed based on 2–3 soil properties with coefficients of determination (R 2 ) of 0.889 and 0.945. Compared with model predicted biosolids Cu HC5input values, current standards (GB4284-84) are most likely to be less protective in acidic and neutral soil, but conservative in alkaline non-calcareous soil. Recommendations on ecological criteria for Cu in land-applied biosolids and biosolid-amended agriculture soils may be helpful to fill the gaps existing between science and regulations, and can be useful for Cu risk assessments in soils amended with biosolids. Highlights: The availability of Cu in biosolids is taken into account in deriving biosolids Cu criteria. The ecological criteria for Cu in land-used biosolids can be predicted by soil CEC and pH. The ecological criteria for Cu in biosolid-amended agriculture soils were derived.